Reliability of isometric and isokinetic trunk flexor strength using a functional electromechanical dynamometer - Rodriguez-Perea, A.; Chirosa Rios, L. J.; Martinez-Garcia, D.; Ulloa-Diaz, D.; Guede Rojas, F.; Jerez-Mayorga, D.; Chirosa Rios, I. J. (PeerJ, 2019)
Aim: To determine the absolute and relative reliability of functional trunk tests, using a functional electromechanical dynamometer to evaluate the isokinetic strength of trunk flexors and to determine the most reliable assessment condition, in order to compare the absolute and relative reliability of mean force and peak force of trunk flexors and to determine which isokinetic condition of evaluation is best related to the maximum isometric. Methods: Test-retest of thirty-seven physically active male student volunteers who performed the different protocols, isometric contraction and the combination of three velocities (V1 = 015 m s-1 , V2 = 0.30 m s-1, V3 = 0.45 m s-1) and two range of movement (R1 = 25% cm ; R2 = 50% cm) protocols. Results: All protocols to evaluate trunk flexors showed an absolute reliability provided a stable repeatability for isometric and dynamic protocols with a coefficient of variation (CV) being below 10% and a high or very high relative reliability (0.69 < intraclass correlation coefficient [ICC] > 0.86). The more reliable strength manifestation (CV = 6.82%) to evaluate the concentric contraction of trunk flexors was mean force, with 0.15 m s-1 and short range of movement (V1R1) condition. The most reliable strength manifestation to evaluate the eccentric contraction of trunk flexors was peak force, with 0.15 m s-1 and a large range of movement (V1R2; CV = 5.07%), and the most reliable way to evaluate isometric trunk flexors was by peak force (CV = 7.72%). The mean force of eccentric trunk flexor strength with 0.45 m s-1 and short range of movement (V3R1) condition (r = 0.73) was best related to the maximum isometric contraction. Conclusion: Functional electromechanical dynamometry is a reliable evaluation system for assessment of trunk flexor strength.